THE INFLUENCE OF AWARENESS, TRIAL, PREFERENCE, DEVOTION, AND FANATICISM ON THE REPURCHASE INTENTION OF INDOMIE PRODUCTS - Qital, Dari Aulia; Munandar, Jono M.; Aidi, Muhammad Nur (Jurnal Aplikasi Manajemen, 2023)
The purpose of this study is to analyze the level and influence of awareness, trial, preference, devotion and fanaticism of Indomie customers in Jabodetabek. The research was carried out using an online questionnaire given to respondents who were consumers of Indomie products in Jabodetabek. Based on the descriptive analysis of Indomie consumers in Jabodetabek, the level of awareness is very good, the level of trial is good, the level of preference is good, the level of devotion and fanaticism tends to be quite good. As for purchase intention, purchase decision and repurchase intention, they are included in the fairly good criteria. Judging from the results of the hypothesis testing, it is known that The results indicate that awareness significantly influences both purchase intention and purchase decision. Similarly, trial positively impacts purchase intention and purchase decision. Furthermore, preference has a significant effect on purchase intentions but not on purchase decisions. The findings also reveal that preference does significantly affect repurchase intention. Devotion significantly influences the repurchase decision. But contrary to expectations, devotion does not affect repurchase intentions. Similarly, fanaticism has no significant effect on purchase decisions. Lastly, the study confirms that fanaticism influences repurchase intention, purchase intention influences purchase decision, and purchase decision positively affects repurchase intention. That highlights the importance of the initial purchase decision in shaping future repeat purchases.